2023
DOI: 10.1029/2023gl105672
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in September Arctic Sea Ice Predictions Via Assimilation of Summer CryoSat‐2 Sea Ice Thickness Observations

Yong‐Fei Zhang,
Mitchell Bushuk,
Michael Winton
et al.

Abstract: Because of a spring predictability barrier, the seasonal forecast skill of Arctic summer sea ice is limited by the availability of melt‐season sea ice thickness (SIT) observations. The first year‐round SIT observations, retrieved from CryoSat‐2 from 2011 to 2020, are assimilated into the GFDL ocean–sea ice model. The model's SIT anomaly field is brought into significantly better agreement with the observations, particularly in the Central Arctic. Although the short observational period makes forecast assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…Min et al (2023) demonstrated that assimilation of summer SIT corrects the overestimation in the Combined Model and Satellite Thickness (CMST; Mu et al, 2018b) product. Y.-F. Zhang et al (2023) found that the assimilation of May to August CryoSat-2 SIT anomalies improves local SIC and sea-ice extent (SIE) forecasts in September. However, the influence of assimilating summer CryoSat-2 SIT observations on short-term sea-ice forecast in summer and on long-term forecast extending beyond September still needs further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Min et al (2023) demonstrated that assimilation of summer SIT corrects the overestimation in the Combined Model and Satellite Thickness (CMST; Mu et al, 2018b) product. Y.-F. Zhang et al (2023) found that the assimilation of May to August CryoSat-2 SIT anomalies improves local SIC and sea-ice extent (SIE) forecasts in September. However, the influence of assimilating summer CryoSat-2 SIT observations on short-term sea-ice forecast in summer and on long-term forecast extending beyond September still needs further investigation.…”
Section: Introductionmentioning
confidence: 99%